POSTOPERATIVE DELIRIUM: WHAT NEW DOES NOVEL GUIDELINES BY ESA-2017 OFFER? - V. V. Likhvantsev; O. N. Ulitkina; N. A. Rezepov (Вестник анестезиологии и реаниматологии, 2018)
Postoperative delirium is being actively discussed by anesthesiologists for a long period of time. This article has been written due to new guidelines on prevention and management of this disorder compiled by the group of experts under umbrella of European Society of Anaesthesiology. Comparing this edition with the previous recommendations of American Society of Anesthesiologists the authors attempt to follow the evolution of doctors' views (anesthesiologists and intensive care physicians) on the discussed issue.